Inflammatory Immune-Associated eRNA: Mechanisms, Functions and Therapeutic Prospects - Wan, Lilin; Li, Wenchao; Meng, Yuan; Hou, Yue; Chen, Ming; Xu, Bin (Frontiers in Immunology, 2022)
The rapid development of multiple high-throughput sequencing technologies has made it possible to explore the critical roles and mechanisms of functional enhancers and enhancer RNAs (eRNAs). The inflammatory immune response, as a fundamental pathological process in infectious diseases, cancers and immune disorders, coordinates the balance between the internal and external environment of the organism. It has been shown that both active enhancers and intranuclear eRNAs are preferentially expressed over inflammation-related genes in response to inflammatory stimuli, suggesting that enhancer transcription events and their products influence the expression and function of inflammatory genes. Therefore, in this review, we summarize and discuss the relevant inflammatory roles and regulatory mechanisms of eRNAs in inflammatory immune cells, non-inflammatory immune cells, inflammatory immune diseases and tumors, and explore the potential therapeutic effects of eRNA-targeted drugs for diseases with inflammatory immune responses.